Product-focused software process improvement : 19th International Conference, PROFES 2018, Wolfsburg, Germany, November 28-30, 2018, Proceedings /: 19th International Conference, PROFES 2018, Wolfsburg, Germany, November 28-30, 2018, Proceedings. (2018) - Unknown
No abstract available